Integration Questions

Question Number 98016 by bemath last updated on 11/Jun/20

$$\underset{\mathrm{0}} {\overset{\mathrm{1}} {\int}}\:\frac{\mathrm{ln}^{\mathrm{2}} \left({x}\right)}{{x}^{\mathrm{2}} +\mathrm{1}}\:{dx}\:?\: \\$$

Commented by bobhans last updated on 11/Jun/20

$$\mathrm{substitution}\:{w}\:=\:−\mathrm{ln}\:\left({x}\right)\:,\:{x}\:=\:{e}^{−{w}} \\$$$${I}=\:\underset{\infty} {\overset{\mathrm{0}} {\int}}\:\frac{\left(−\mathrm{w}\right)^{\mathrm{2}} }{\mathrm{1}+\left(\mathrm{e}^{−\mathrm{w}} \right)^{\mathrm{2}} }\:\left(−\mathrm{e}^{−\mathrm{w}} \:\mathrm{dw}\right) \\$$$$\mathrm{I}=\:\underset{\mathrm{0}} {\overset{\infty} {\int}}\:\mathrm{w}^{\mathrm{2}} .\frac{\mathrm{e}^{−\mathrm{w}} }{\mathrm{1}+\mathrm{e}^{−\mathrm{2w}} }\:\mathrm{dw}\: \\$$$$\left[\:\frac{\mathrm{e}^{−\mathrm{w}} }{\mathrm{1}+\mathrm{e}^{−\mathrm{2w}} }\:=\:\underset{\mathrm{n}\:=\mathrm{0}} {\overset{\infty} {\sum}}\left(−\mathrm{1}\right)^{\mathrm{n}−\mathrm{1}} \:\mathrm{e}^{−\left(\mathrm{2n}+\mathrm{1}\right)\mathrm{w}} \:\right] \\$$$$\mathrm{I}=\:\underset{\mathrm{n}=\mathrm{1}} {\overset{\infty} {\sum}}\left(−\mathrm{1}\right)^{\mathrm{n}} \:\underset{\mathrm{0}} {\overset{\infty} {\int}}\:\left(\frac{\mathrm{t}}{\mathrm{2n}+\mathrm{1}}\right)^{\mathrm{2}} \mathrm{e}^{−\mathrm{t}} \:\frac{\mathrm{dt}}{\mathrm{2n}+\mathrm{1}};\: \\$$$$\mathrm{where}\:\mathrm{t}\:=\:\left(\mathrm{2n}+\mathrm{1}\right)\mathrm{w}\: \\$$$$\mathrm{I}=\:\underset{\mathrm{n}=\mathrm{0}} {\overset{\infty} {\sum}}\:\frac{\left(−\mathrm{1}\right)^{\mathrm{n}} }{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{3}} }\:\underset{\mathrm{0}} {\overset{\infty} {\int}}\:\mathrm{t}^{\mathrm{2}} \:\mathrm{e}^{−\mathrm{t}} \:\mathrm{dt}\: \\$$$$\mathrm{I}=\:\underset{\mathrm{n}=\mathrm{0}} {\overset{\infty} {\sum}}\:\frac{\left(−\mathrm{1}\right)^{\mathrm{n}} }{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{3}} }\:.\mathrm{2}!\:\:=\:\mathrm{2}\:×\:\underset{\mathrm{n}=\mathrm{0}} {\overset{\infty} {\sum}}\:\frac{\left(−\mathrm{1}\right)^{\mathrm{n}} }{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{3}} } \\$$$$\mathrm{I}=\:\mathrm{2}×\:\:\frac{\pi^{\mathrm{3}} }{\mathrm{32}}\:=\:\frac{\pi^{\mathrm{3}} }{\mathrm{16}}\:\blacksquare\: \\$$

Commented by  M±th+et+s last updated on 11/Jun/20

$${go}\:{to}\:{Q}.\mathrm{97369} \\$$

Commented by bemath last updated on 13/Jun/20

$$\mathrm{greatt} \\$$

Answered by mathmax by abdo last updated on 11/Jun/20

$$\mathrm{I}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:\frac{\mathrm{ln}^{\mathrm{2}} \mathrm{x}}{\mathrm{x}^{\mathrm{2}} \:+\mathrm{1}}\mathrm{dx}\:\Rightarrow\mathrm{I}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{ln}^{\mathrm{2}} \left(\mathrm{x}\right)\left(\sum_{\mathrm{n}=\mathrm{0}} ^{\infty} \left(−\mathrm{1}\right)^{\mathrm{n}} \:\mathrm{x}^{\mathrm{2n}} \right)\mathrm{dx} \\$$$$=\sum_{\mathrm{n}=\mathrm{0}} ^{\infty} \:\left(−\mathrm{1}\right)^{\mathrm{n}} \:\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{ln}^{\mathrm{2}} \mathrm{x}\:\mathrm{x}^{\mathrm{2n}} \:\mathrm{dx}\:\:\mathrm{let}\:\mathrm{A}_{\mathrm{n}} =\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{ln}^{\mathrm{2}} \mathrm{x}\:\mathrm{x}^{\mathrm{2n}} \:\mathrm{dx}\:\mathrm{changement}\:\mathrm{lnx}\:=−\mathrm{t} \\$$$$\mathrm{give}\:\mathrm{A}_{\mathrm{n}} =−\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{2}} \left(\mathrm{e}^{−\mathrm{t}} \right)^{\mathrm{2n}} \:\left(−\mathrm{e}^{−\mathrm{t}} \right)\mathrm{dt} \\$$$$=\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{2}\:} \:\mathrm{e}^{−\left(\mathrm{2n}+\mathrm{1}\right)\mathrm{t}} \:\mathrm{dt}\:=_{\left(\mathrm{2n}+\mathrm{1}\right)\mathrm{t}\:=\mathrm{u}} \:\:\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{u}^{\mathrm{2}} }{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{2}} }\:\mathrm{e}^{−\mathrm{u}} \:\:\frac{\mathrm{du}}{\left(\mathrm{2n}+\mathrm{1}\right)} \\$$$$=\frac{\mathrm{1}}{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{3}} }\:\int_{\mathrm{0}} ^{\infty} \:\mathrm{u}^{\mathrm{2}} \:\mathrm{e}^{−\mathrm{u}} \mathrm{du}\:\:\mathrm{but}\:\:\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{\mathrm{x}−\mathrm{1}} \:\mathrm{e}^{−\mathrm{t}} \:\mathrm{dt}\:=\Gamma\left(\mathrm{x}\right)\:\Rightarrow\int_{\mathrm{0}} ^{\infty} \:\mathrm{u}^{\mathrm{2}} \:\mathrm{e}^{−\mathrm{u}} \:\mathrm{du}\:=\Gamma\left(\mathrm{3}\right)=\mathrm{2}!=\mathrm{2} \\$$$$\Rightarrow\mathrm{A}_{\mathrm{n}} =\frac{\mathrm{2}}{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{3}} }\:\Rightarrow\:\mathrm{I}\:=\mathrm{2}\:\sum_{\mathrm{n}=\mathrm{0}} ^{\infty} \:\frac{\left(−\mathrm{1}\right)^{\mathrm{n}} }{\left(\mathrm{2n}+\mathrm{1}\right)^{\mathrm{3}} }\:\mathrm{rest}\:\mathrm{to}\:\mathrm{calculate}\:\mathrm{this}\:\mathrm{serie}\:\mathrm{by}\:\mathrm{fourier}... \\$$